Faces in the crowd - Luiselli, Valeria, 1983- (Coffee House Press, 2014)
A multi-layered story told by two narrators: a 21st-century Emily Dickinson living in Mexico City who relates to the world vicariously through her children and a past that both overwhelms and liberates her, and a dying poet living in a run-down apartment in Philadelphia in the 1950s. While she tells the story of her past as a young editor in New York City desperately trying to convince a publisher to translate and publish the works of Gilberto Owen-an obscure Mexican poet who lived in Harlem during the 1920s and whose ghostly presence constantly haunts her in the subway-she also relates the slow but inevitable disintegration of her present family life.